Lexical Cohesion in English – Indonesia Machine Translation Output: The Realization of Manual Post-Editing - Sugiarto, Bambang Ruby; Siregar, Bahren Umar (JALL (Journal of Applied Linguistics and Literacy), 2023)
Lexical cohesion is fundamentally dependent on linguistic cohesiveness. However, whether lexical coherence remains as texts are translated from English into Indonesian has yet to be determined. Considering this, the purpose of this study was to characterize the structure of the lexical cohesion in English-Indonesia Machine Translation (MT), and Post-Editing (PE) outputs and determine whether there were any differences in the use of lexical cohesion. A qualitative descriptive study was conducted. The fifth book in J.K. Rowling's (2013) Harry Potter and the Order of the Phoenix contains the data used in this study. Baker’s (2018) equivalence at the word, above word, grammatical, and textual level, and Halliday & Matthiessen (2014) model of lexical cohesion were used to analyze and interpret the data. It was found that there aren't many differences between the lexical cohesion used in the ST, MT, and PE. While the study explores the application of lexical cohesion, additional problem equivalences, such as those at the word and above-word levels, are added to the PE recommendation.